A facile synthesis of norathyriol. (1st January 2013) - Qin, Qi-xue; Yang, Jian; Yang, Bo; Liu, Man; Xiao, Dan; Yang, Xuemin
In this paper, norathyriol has been synthesised from 2-bromo-4, 5-dimethoxybenzoic acid and 1, 3, 5-trimethoxybenzene by a three-step sequence of transformations involving a Friedel–Crafts acylation with cyclisation and demethylation. The procedure was facile and should be easily scaled-up. The overall yields reached approximately 70%.